Representing 9/11: Journalism and autobiography in the work of Alexander Osang - van der Knaap, E.W. (Maney Publishing, 2018)
The article analyses the modes of representation used by the GDR-born journalist Alexander Osang in writing about 9/11. His observations of 9/11 in New York open up recollections of 11/9, the historic date in 1989 when the Berlin Wall fell. His gaze is compared to the way his wife observes. The authentic tone and the self-referential mode raise questions about relevance in literature.
Keywords: 9/11; Terrorism; Representation; Journalism; Autobiography; Osang; Literature and Literary Theory; SDG 16 - Peace, Justice and Strong Institutions